MetR-Regulated Vibrio cholerae Metabolism Is Required for Virulence - Ryan W. Bogard (American Society for Microbiology, 2012)
ABSTRACT LysR-type transcriptional regulators (LTTRs) are the largest, most diverse family of prokaryotic transcription factors, with regulatory roles spanning metabolism, cell growth and division, and pathogenesis. Using a sequence-defined transposon mutant library, we screened a panel of V. cholerae El Tor mutants to identify LTTRs required for host intestinal colonization. Surprisingly, out of 38 LTTRs, only one severely affected intestinal colonization in the suckling mouse model of cholera: the methionine metabolism regulator, MetR. Genetic analysis of genes influenced by MetR revealed that glyA1 and metJ were also required for intestinal colonization. Chromatin immunoprecipitation of MetR and quantitative reverse transcription-PCR (qRT-PCR) confirmed interaction with and regulation of glyA1, indicating that misregulation of glyA1 is likely responsible for the colonization defect observed in the metR mutant. The glyA1 mutant was auxotrophic for glycine but exhibited wild-type trimethoprim sensitivity, making folate deficiency an unlikely cause of its colonization defect. MetJ regulatory mutants are not auxotrophic but are likely altered in the regulation of amino acid-biosynthetic pathways, including those for methionine, glycine, and serine, and this misregulation likely explains its colonization defect. However, mutants defective in methionine, serine, and cysteine biosynthesis exhibited wild-type virulence, suggesting that these amino acids can be scavenged in vivo. Taken together, our results suggest that glycine biosynthesis may be required to alleviate an in vivo nutritional restriction in the mouse intestine; however, additional roles for glycine may exist. Irrespective of the precise nature of this requirement, this study illustrates the importance of pathogen metabolism, and the regulation thereof, as a virulence factor. IMPORTANCE Vibrio cholerae continues to be a severe cause of morbidity and mortality in developing countries. Identification of V. cholerae factors critical to disease progression offers the potential to develop or improve upon therapeutics and prevention strategies. To increase the efficiency of virulence factor discovery, we employed a regulator-centric approach to multiplex our in vivo screening capabilities and allow whole regulons in V. cholerae to be interrogated for pathogenic potential. We identified MetR as a new virulence regulator and serine hydroxymethyltransferase GlyA1 as a new MetR-regulated virulence factor, both required by V. cholerae to colonize the infant mouse intestine. Bacterial metabolism is a prerequisite to virulence, and current knowledge of in vivo metabolism of pathogens is limited. Here, we expand the known role of amino acid metabolism and regulation in virulence and offer new insights into the in vivo metabolic requirements of V. cholerae within the mouse intestine.